Design and Implementation of Accurate Foot drop Prosthesis System - Abbas Fadhal Humadi; Luban Hamdy Hameed; Zainab Majid Nahy (Journal of Madenat Alelem University College, 2016)
In present study, an accurate foot drop prosthesis device is presented. The design of the proposed system depends on electrical stimulation generated by electronic stimulator within specific requirements. This train of pulses that delivered to the targeted group of muscles innervate by pearonal nerve, using adhesive surface electrodes, has effective voltage amplitude, duration and frequency to stimulate these muscles to lift the dropped foot of the ground effectively during the swing phase of the gait cycle. The operation begins when the patient start to walk, so starting of the swing phase will be sensed using pressure sensor located under the heel of the patient’s dropped foot. In this case, the electronic stimulator will be activated by the pressure sensor to start sending the stimuli that activate the muscles to lift the dropped foot causing the gate to be balanced and normal. Results shows that the output wave form of the stimulator is biphasic type pulse wave of net charge close to zero, with maximum voltage amplitude of 90V, frequency of 62Hz, and duration of 600ms.The current delivered to the muscles will be dependent on the tissue impedance and the voltage assigned for stimulation. This output pulses will be comfortable to the patient and cause accurate effective stimulation to the targeted group of muscles, leads to cancel the effect of dropped foot.